ZnO Nanosheets Exhibiting High UV Blocking Efficiency for Effective Application in Sunscreen - Sahu, Dojalisa; Panda, Nihar R.; Dash, Debasrita (Asian Journal of Chemistry, 2020)
Zinc oxide (ZnO) nanopowder has been prepared by wet chemical method and tested for its effective UV blocking property coated on photosensitive paper/fabric samples. Zinc acetate dihydrate and ammonium hydroxide were adopted as synthesis precursors. Phase and crystallographic analysis of the samples have been carried out by X-ray diffraction (XRD) and show that ZnO sample belong to hexagonal wurtzite phase without any impurity. Surface morphology of ZnO samples studied by field emission scanning electron microscopy (FESEM) shows the formation of nanosheets with porous structure. These porous nanosheets have surface area varying from 5000-30000 nm2 with thickness 10-15 nm. ZnO nanosheets on the photosensitive paper show UV absorbance around 300 nm as observed from the absorption spectrum. The reflectance spectrum of ZnO also shows its effectiveness in reflecting UV light in the region of 350-400 nm. The sun protection factors (SPF) and ultraviolet protection factors (UPF) calculated from the above studies are also encouraging implicating the use of ZnO in sunscreen. The above experiment is carried out by preparing a photosensitive layer similar to human skin. Similar experiment has also been carried out by treating ZnO nanosheets on fabric samples and studying its effectiveness for protection from UV rays.